Needs and expectations of inbound tourists visiting a peripheral area : a case study in northern Sweden - Kvist, Anna-Karin (Luleå, 2005)
Tourism is the world's largest industry. It has power to change communities and has a large societal impact. The tourism industry is rapidly growing and by 2011 it is projected to generate 7.0 trillion USD of economic activity and 260 million jobs over the world. In Sweden consumption by tourists grew to about 16,500 USD in 2001 or by 10% from the preceding year. From 1997 that is a growth by almost 25%. During 2001 more than 127,000 people worked in the tourism industry, calculated as whole year employment. The tourism industry is the only export industry in Sweden to supply Government finance with more than 667 million USD in value-added taxes. Seen in that perspective, the tourism industry will be an important income source, not the least in peripheral areas, if utilized sufficiently well. However, to be successful it is important to understand the needs and expectations of those tourists you want to attract and then also satisfy, or preferably exceed, those needs and expectations. The purpose of this thesis is mainly to explore needs and expectations of inbound tourists, which deals with visits to a country by non-residents, visiting a peripheral area, and see how these needs and expectations are fulfilled during the stay. From that it is possible to explore how customer satisfaction can be measured in the tourism sector and thereby contribute to improvement work in that sector. In the thesis a number of Italian and British tourists visiting Northern Sweden are studied in a multiple-case study. The three cases are related to different time perspectives of the journey. The first case deals with the needs and expectations the tourists have before the visit. These were investigated by questionnaires distributed to the tourists before their arrival. The second case is the experiences during the stay. These were gathered from interviews. The third case is related to the impression and experiences the tourists had when they were back home again and these were collected using a second questionnaire. Different ...